2004
DOI: 10.1007/s00464-004-9067-7
|View full text |Cite
|
Sign up to set email alerts
|

Open vs laparoscopic repair of secondary lumbar hernias: a prospective nonrandomized study

Abstract: The laparoscopic approach to secondary lumbar hernia repair is more efficient and more profitable than the traditional open technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 10 publications
0
88
0
9
Order By: Relevance
“…Surgery is usually the recommended treatment. [1] An open procedure is the classic method of repair for lumbar hernias, however, laparoscopic methods are more recently being described and recommended as being the best approach due to the well-known benefits of minimally invasive surgery: shorter length of hospital stay, less pain, and fewer wound complications. [1,4] A prospective nonrandomized study comparing open versus laparoscopic repair of 16 patients who underwent operation for lumbar hernias revealed one hernia recurrence with the open approach and no recurrences with the laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surgery is usually the recommended treatment. [1] An open procedure is the classic method of repair for lumbar hernias, however, laparoscopic methods are more recently being described and recommended as being the best approach due to the well-known benefits of minimally invasive surgery: shorter length of hospital stay, less pain, and fewer wound complications. [1,4] A prospective nonrandomized study comparing open versus laparoscopic repair of 16 patients who underwent operation for lumbar hernias revealed one hernia recurrence with the open approach and no recurrences with the laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…[1] An open procedure is the classic method of repair for lumbar hernias, however, laparoscopic methods are more recently being described and recommended as being the best approach due to the well-known benefits of minimally invasive surgery: shorter length of hospital stay, less pain, and fewer wound complications. [1,4] A prospective nonrandomized study comparing open versus laparoscopic repair of 16 patients who underwent operation for lumbar hernias revealed one hernia recurrence with the open approach and no recurrences with the laparoscopic approach. [1] The study also revealed a significant increase in postoperative morbidity in the open approach, however, in the laparoscopic approach, there was a higher incidence of intraoperative complications (two hematomas and one inferior epigastric artery lesion).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Since the first laparoscopic repair in 1996, 7 at least 40 cases of laparoscopic lumbar hernia repair have been reported. [8][9][10][11][12][13] Lumbotomy hernias are often asymptomatic but usually come to medical attention because of pain, bulging over the incision or altered bowel habits. Provocation manoeuvres such as standing or coughing may cause ballooning.…”
Section: Discussionmentioning
confidence: 99%